Seletividade de inseticidas às diferentes fases de desenvolvimento da tesourinha Doru luteipes (Scudder, 1876) (Dermaptera, Forficulidae) - Simões, Juliana Carvalho (1994)
Doru luteipes (Scudder) is an important predator in the suppression of Spodoptera frugiperda (Smith) in corn. One of the ways to preserve this insect is by the selective use of insecticides. The objective of this work was to evaluate some insecticides over different stages of the predator. Spraying directly over the eggs and the nymphal instars and indirectly spraying over the eggs masses of S. frugiperda and giving theses treated eggs to be eaten by the adult predator. In the first experiment the natural enemy's eggs were placed in Petri dishes and treated with the insecticides, using a sprayerpressurized with C02 at a rate of262 l/ha, over one rolling mat, where the insecticides were sprayed. In the second experiment each nymphal stage of the insect was placed in corn plants, in pots protected by PVC cages, where they were sprayed by a coastal sprayer, at a volume of 200 l/ha. In the third experiment each earwig's nymphal stage were placed in Petri dishes and sprayed with the insecticides over the rolling mat, using the same methodology of experiment 1. The fourth experiment consisted on spraying the eggs of S. frugiperda inside of Petri dishes, and after that giving them to the adults of D. luteipes. The same methodology of experiment 1 and 3 was used. The following insecticides were evaluated: diflubenzuron (Dimilin 250 PM - 150 g p.c./ha), triflumuron (Alsystin 250 PM - 100 g p.c./ha), lambdacyhalothrin (Karate 50 CE - 300 ml/ha), permethrin (Ambush 500 CE - 50 ml/ha), Bacillus thuringiensis (Dipel PM - 500 g/ha) e Baculovírus (Baculovírus) PM - 2,5 x 1011 polyhedrons/ha ). The viability of the D. luteipes eggs varied from 11.1 to 94.4%. There was no difference in the highest viabilities, obtained for the check, Baculovírus and lambdacyhalothrin. The physiological products diflubenzuron and triflumuron were the ones which caused the lowest viabilities of the eggs, with an average 11.1 and 16.7% respectively, having no differences between them. There was no effect of the instars in the experiment conducted in pots and all the insecticides caused significative higher mortality than the one verified in the check, that was of 16.1%. The insecticides that presented higher rate of survival in this experiment were Bacillus thuringiensis and triflumuron having no significative difference between them and the check. In the experiment with nymphs, conducted in the mat, in the average of the insecticides, the lowest rates of mortality were verified for the biological products that did not differ from the check. In all cases, the last instars was the most resistant to the insecticides. In the experiment with adults there was no significative difference among the treatments, showing that the adult insects are resistant to the products when ingested through contaminated eggs. Based on the results it can be concluded that the biological insecticides Baculovírus and Bacillus thuringiensis and the physiological triflumuron and diflubenzuron can be use in integrated management of Spodoptera frugiperda in maize.